Microsomal glucosidases acting on the saccharide moiety of the glucose-containing dolichyl diphosphate oligosaccharide - Ugalde, Rodolfo A. (1979)
The microsomal glucosidases which act on the oligosaccharide that contains 2 N-acetylglucosamine, 9 mannose and 1–3 glucose residues have been studied. Two fractions were separated by differential solubility in detergent and phosphate solutions or by gel filtration. One of the fractions removed glucose from the oligosaccharide containing three glucose residues, and another fraction acted on the compounds containing one and two glucose residues. Both fractions were free of mannosidase. Some properties of the enzymes are described.